Open ankle fractures: Factors influencing unplanned reoperation. Issue 6 (June 2022) - Jaibaji, Monketh; Sohatee, Mark; Watkins, Christopher; Qasim, Sultan; Fearon, Paul
Highlights: Age and quality of soft tissue coverage are key determinants of risk of unplanned reoperation in open ankle fractures. An alternative approach to fixation may need to be adopted in elderly patients with open ankle injuries. Our findings may indicate the need for a lower threshold for soft tissue reconstruction in open ankle fractures may need to be adopted. Abstract: Introduction: Ankle fractures are amongst the most common open fracture injuries presenting to major trauma centres (MTC) and their management remains a topic of debate. Incidence is increasing particularly in the elderly population however the optimal surgical approach and risk factors for unplanned reoperation remain scarce. We therefore conducted a retrospective case study to analyse our institution's outcomes as well as identify risk factors for early unplanned reoperation. Materials and methods: Sixty-five consecutive open ankle fractures were identified using our institutional database between July 2016 and July 2020. Medical records and operation notes were reviewed to identify patient age at injury, Sex, co-morbidities and other co-morbidities, fracture configuration, extent of soft tissue injury, fixation type and post-operative complications. The data was categorised into four groups for analysis, 1) age, 2) AO-OTA classification 3) Sex 4) Gustilo-Anderson grade. Statistical analysis was undertaken to identify predictors of unplanned reoperation. Results: The mean age of patients at the time of injury was 60.8. Unplanned reoperation rate was 17.5%. Age and Gustilo-Anderson classification grade were both statistically significant predictors of unplanned reoperation. AO-OTA classification, Sex and Diabetes were not statistically significant factors associated with unplanned reoperation. Conclusion: Age and quality of soft tissue envelope are significant risk factors for unplanned reoperation. Patients with these risk factors may benefit from an alternative surgical approach.